Arab Media and Political Renewal: Community, Legitimacy and Public Life (L.B. Tauris, 2007)
People are on the move across the Arab world, organizing politically in new ways. The Arab media have also undergone a transformation and are still in a state of flux. It is therefore crucial to be able to discuss political initiatives in the region in the light of media developments. This authoritative book answers key questions about the connections between media and political change in the Arab world. Using research into, for example, practices of Internet users, journalists, demonstrators and producers of reality TV, it explores the interface between public interaction over the airwaves, at the polls and on the streets. A lively group of contributors explores such issues as whether young people are served well by new media, whether blogging is an influential political tool, whether satellite news helps or hinders diasporic communities politically, and much more. Engaging with debates at the heart of public affairs and popular culture in Arab countries, this book addresses everyone who seeks to grasp the media politics of this central, often misunderstood region